Economia solidária: O impacto da Secretaria Nacional de Economia Solidária na região do Baixo Amazonas. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
In Europe in the mid-18th century, long working hours, exploitation in factories, the spread of misery, inequality and individualism were threatening workers' health. In this context, the Solidarity Economy emerged at a time when workers were increasingly organizing themselves to combat the capitalist arrangements structured by the bourgeois class. Based on self-management and solidarity, SE promotes a new economic alternative, organizing itself into solidarity economic enterprises. SE emerged in Brazil during the unemployment crisis in the 1980s and 1990s through social movements such as the Unified Workers’ Central (Central Única dos Trabalhadores – CUT) and Landless Workers’ Movement (Movimento Sem Terra - MST), and gradually the term became more popular until it reached associations of producers, enterprises and popular cooperatives. Years later, in 2003, the social movements, following the World Social Forum, promoted the creation of the National Working Group on Solidarity Economy, which directly demanded that the federal government create a place for SE, which became the National Secretariat for Solidarity Economy (SENAES). SENAES has played a fundamental role in building public policies for SE in Brazil. In the Northern region, specifically in the Lower Amazon, it played a major role in the formation of the pioneering solidarity economy program in Santarem, the Solidarity Economy School, and its teaching materials helped the Incubator of the Federal University of Western Pará (UFOPA) and the Forum of Solidarity Economy of the Lower Amazon.
Keywords: Economia Solidária; Empreendimentos Econômicos Solidários; Alternativa Econômica; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS